Assessments performed on harder surfaces can misrepresent ACL injury risk - Jones, H. S. R.; Stiles, V. H.; Verheul, J.; Moore, I. S. (Sports Biomechanics, 2023)
Changes in surface hardness are likely to alter an athlete`s movement strategy. Anterior cruciate ligament (ACL) injury risk assessments that are performed on a different surface to that used for training and competition may, therefore, not represent an athlete`s on-field movement strategies. The aim of this study was to examine the influence of surface hardness on multidirectional field sport athletes` movement strategies in movements that are commonly used in ACL injury risk assessments (bilateral and unilateral drop jumps, and a cutting manoeuvre). Ground reaction forcesand three-dimensional lower limb kinematics were recorded from 19 healthy, male, multidirectional field sport athletes performing bilateral and unilateral drop jumps, and a 90° cutting task on Mondo track (harder surface) and artificial turf (softer surface). Continuous (statistical parametric mapping) and discrete analyses revealed alterations in vertical and horizontal braking forces and knee and hip moments between surfaces of different hardness in all three movements (p = 0.05, d > 0.5). Injury risk assessments performed on a harder surface (e.g. Mondo track) can misrepresent an athlete`s risk of ACL injury compared to the same movements performed on a softer more cushioned surface that is typically used for training and/or matches (e.g. artificial turf).